Debt Relief for Poverty Reduction : The Role of the Enhanced HIPC Initiative - Irving, Jacqueline (Pamphlet Series; Pamphlet Series, No., 2001)
This pamphlet reports on how the enhanced Initiative for Heavily Indebted Poor Countries (HIPCs) is meeting its aim of delivering faster, broader, and deeper debt relief to more HIPCs once these countries have shown a commitment to put the freed-up funds to work for the poor. The pamphlet also includes introductory sections that explain the rationale for the HIPC Initiative and describe how it works. A concluding section discusses the Initiative's top challenge in the year ahead: to bring the remaining eligible countries to their decision points under the Initiative as fast and realistically as possible.